Mapping Welfare Diversity: A Regional Analysis of Türkiye’s Welfare Regime through Esping-Andersen’s Welfare Regimes Typology - Özdemir, Nurten Ebru; Sarıipek, Doğa Başar; Cerev, Gökçe; Akturan, Abdülkadir (Social Welfare: Interdisciplinary Approach, 2025)
This study develops a comprehensive regional welfare map of Türkiye by using Esping-Andersen’s welfare typologies with the objective to analyze regional variations in welfare policies. By focusing on poverty and unemployment as key indicators, the research categorizes Türkiye’s welfare systems at both macro and micro levels, offering valuable insights for shaping future social welfare policies. A total of 243 semi-structured interviews were conducted across all 81 provinces with Non-Governmental Organizations (NGOs) selected based on their involvement in welfare-related activities. The data, analyzed by using Maxqda software, reveals that Turkey exhibits a hybrid welfare system, incorporating liberal, conservative, and social democratic elements, with significant regional disparities. NGOs play a critical role in bridging gaps in the State welfare provision, particularly in regions with limited State intervention. Supported by the Scientific and Technological Research Council of Turkey (TÜBİTAK), this study makes a significant contribution to the welfare typology literature and provides practical insights for reducing regional inequalities.
Keywords: Regional welfare map; poverty; unemployment; welfare typologies; welfare regime in Turkey